Environmental impacts assessment of ethanol production using method derived from the Leopold Matrix - Almeida, Samara Rodrigues de; Santos, Vivianni Marques Leite dos; Torres, Gabriel Pilé de Barros (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this paper the ethanol production process was analyzed, identifying environmental impacts caused as a consequence, targeting the maximization of the positive impacts and reduce those negatives. For this analysis, a matrix derived from the Leopold matrix was prepared. This matrix takes into account the various stages of production, facilitating the visualization of the origin of each impact, allowing the minimization of the impacts through changes in the process. The initial matrix was compared with a new matrix prepared from proposed actions to check the environmental gains. The use of the straw for power generation, adding purification filters, the installation of a sewage water treatment and reducing losses during the process were the proposed alternative measures. The impacts were analyzed according to criteria of order, time, dynamics and plasticity. Comparatively, it was observed that the actions proposals for the impact mitigation and control can promote positive impacts and reduce negative impacts significantly. Furthermore, the use of the method derived form the Leopold Matrix proved a promising tool for decision making both in companies and universities.